Odonata as potential bioindicator to assess different habitat quality in terrestrial landscape - Yahya, Nor Afifah (2019)
Monoculture practice is increasing rapidly in Malaysia due to massive expansion of oil palm and rubber plantations. Due to this, massive forests have been converted into agricultural land. This resulted to major changes in landscape structure that causes overall biodiversity decline particularly insects. The present study was conducted to measure habitat quality of different agricultural systems in orchard, oil palm, and rubber plantations and its impact on dragonfly and damselfly (Insecta: Odonata) abundance and species richness. The study was conducted at Kampung Ulu Sepri, Kampung Empang Batu and Kampung Batang Sepri located in Pedas, Negeri Sembilan. Odonata sampling was carried out using visual observation in 30 sampling points for each agricultural landscape (a total of 90 sampling points). In overall, 1,375 Odonata individuals belonging to 55 species and 8 families were recorded. In this study, orchards recorded the highest Odonata abundance with 41% followed by rubber plantations and oil palm plantations with 36% and 23% respectively. Rubber plantations recorded the highest species richness with 44% followed by orchards and oil palm plantations with 33% and 23% respectively. The findings showed that Odonata abundance in orchard was greater than monoculture plantation due to better habitat quality. While, greater Odonata species richness in rubber plantations was due to species spill over from adjacent forest area. In conclusion, Odonata from the family Calopterygidae and Chlorocyphidae can provide suitable biological indicator for habitat disturbance. Odonata occurence in both monoculture and polyculture systems require paramount importance for insect conservation.